Effects of Anodic Buffer Layer in Top-Illuminated Organic Solar Cell with Silver Electrodes - Tien-Lung Chiu; Himadri Mandal; Mi Zhang; Shun-Po Yang; Ya-Ting Chuang (International Journal of Photoenergy)
An efficient ITO-free top-illuminated organic photovoltaic (TOPV) based on small molecular planar heterojunction was achieved by spinning a buffer layer of poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS), on the Ag-AgOx anode. The PEDOT:PSS thin film separates the active layer far from the Ag anode to prevent metal quenching and redistributes the strong internal optical field toward dissociated interface. The thickness and morphology of this anodic buffer layer are the key factors in determining device performances. The uniform buffer layer contributes a large short-circuit current and open-circuit voltage, benefiting the final power conversion efficiency (PCE). The TOPV device with an optimal PEDOT:PSS thickness of about 30 nm on Ag-AgOx anode exhibits the maximum PCE of 1.49%. It appreciates a 1.37-fold enhancement in PCE over that of TOPV device without buffer layer.